Meganyctiphanes norvegica ... - Grams, Markus; Klinger, Michael; Richter, Stefan (Zenodo, 2023)
MEGANYCTIPHANES NORVEGICA The first pair of thoracopods (Fig. 7A) to Thp7 are all similar, whereas Thp8 is vestigial. The following descriptions are based on a detailed examination of the right Thp1 of three adult females of M. norƲegica . Cuticle and skeletal structures of thoracopods in M. norvegica The following description refers collectively to Thp1–7, if not specified otherwise. The ventral cuticle of the first thoracomere is coalesced with that of the cephalon. The density of the cuticle of this cephalothoracic sternum appears higher than in the posterior thoracomeres. Anteriorly, the thoracic cuticle articulates with the maxilla, which is tightly fitted against the anterior wall of the coxa and basis of Thp1. In all thoracomeres, the posterior thoracic cuticle is folded in an anterior direction, forming a broad roof-like apodeme (partly dashed curved arrow in Fig. 7B, C) of moderate density that hangs over the posterior half of the proximal foramen of the leg (i.e. of the coxa). Medially, the cuticle ... : Published as part of Grams, Markus, Klinger, Michael & Richter, Stefan, 2023, Neither leg nor jaw-nor always the same: a critical revision of the eumalacostracan maxilliped, pp. 965-1004 in Zoological Journal of the Linnean Society 197 (4) on pages 974-981, DOI: 10.1093/zoolinnean/zlac083, http://zenodo.org/record/7797605 ...